Electrical spinal cord stimulation must preserve proprioception to enable locomotion in humans with spinal cord injury. (December 2018) - Formento, Emanuele; Minassian, Karen; Wagner, Fabien; Mignardot, Jean; Le Goff-Mignardot, Camille; Rowald, Andreas; Bloch, Jocelyne; Micera, Silvestro; Capogrosso, Marco; Courtine, Gregoire
Abstract Epidural electrical stimulation (EES) of the spinal cord restores locomotion in animal models of spinal cord injury but is less effective in humans. Here we hypothesized that this interspecies discrepancy is due to interference between EES and proprioceptive information in humans. Computational simulations and preclinical and clinical experiments reveal that EES blocks a significant amount of proprioceptive input in humans, but not in rats. This transient deafferentation prevents modulation of reciprocal inhibitory networks involved in locomotion and reduces or abolishes the conscious perception of leg position. Consequently, continuous EES can only facilitate locomotion within a narrow range of stimulation parameters and is unable to provide meaningful locomotor improvements in humans without rehabilitation. Simulations showed that burst stimulation and spatiotemporal stimulation profiles mitigate the cancellation of proprioceptive information, enabling robust control over motor neuron activity. This demonstrates the importance of stimulation protocols that preserve proprioceptive information to facilitate walking with EES. Electrical spinal cord stimulation interferes with natural proprioceptive information in humans. Ecological stimulation protocols that preserve limb position awareness and proprioceptive circuit dynamics facilitate walking after spinal cord injury.